Estrategias didácticas activas para la mejora del proceso de enseñanza-aprendizaje de Ciencias Naturales. Año lectivo 2023-2024. - Villa Yunga, Angela Yulissa (2024)
The implementation of active didactic strategies in the development of the teaching-learning process of Natural Sciences is important, because it allows fostering the active participation and interest of students to learn the scientific content of the subject, thus enhancing their academic performance. The research had as objective: <<Potentiate the academic performance of students through the implementation of active didactic strategies that allow improving the teaching-learning process of Natural Sciences, of tenth year of GBE, of "27 de Febrero" High school, academic year 2023-2024>>>. For this, the inductive method was used, since, it began with the direct observation of the development of the TLP, evidencing the lack of implementation of active didactic strategies. This led to a bibliographic search to find alternative solutions to the problem identified. In addition, the approach was qualitative, important characteristics of the development of the classroom process were determined, which guided the intervention actions. According to the nature of the information, it corresponds to Participatory Action Research (PAR). The defined problem was directly intervened, through the implementation of active didactic strategies during the development of the intervention proposal, in which students were actively involved, thus improving their academic performance. According to the temporality it is of a transversal type, so the research work was carried out in a short period of time. The results obtained allowed establishing that the active didactic strategies implemented in the development of the TLP: Gamification, visual thinking, active learning and learning stations, promoted the active participation of students, significantly improving their academic performance. In this sense, it is concluded that the academic performance of students is enhanced through the implementation of active didactic strategies that improve the teaching-learning process of Natural Sciences. Key words: Active participation, academic performance, didactic techniques, meaningful learning.